PENGARUH DAN PERAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERUSAHAAN TERHADAP KESEJAHTERAAN EKONOMI MASYARAKAT : Corporate Social Responsibility Perusahaan Terhadap Kesejahteraan Ekonomi Masyarakat - Ariani, Taufiqoh Bina; Setiady, Tri; Abas, Muhamad; Budi Santoso, Imam (Fakultas Hukum Universitas Jambi, 2023)
The work of the Corporate Social Obligation organization is required in the financial success of the local region in order to aid the community's economy, which combines diverse points of view. so that business in society is not perceived as a danger to the environment and solely has an interest in obtaining profit. The effect of the Corporate Social Responsibility program must be accountable in strengthening the community's economy, according to Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies. The author poses the following questions: